Prognostic Value of Tumor-Infiltrating Lymphocytes Differs Depending on Lymphocyte Subsets in Esophageal Squamous Cell Carcinoma: An Updated Meta-Analysis - Hao, Jiatao; Li, Meng; Zhang, Taohong; Yu, Hui; Liu, Ying; Xue, Yan; An, Ruifang; Wang, Shuai (Frontiers in Oncology, 2020)
Background: Tumor-infiltrating lymphocytes (TILs) play a role in the anti-tumor immune response, and are often found in esophageal squamous cell carcinoma (ESCC). Methods: We performed a systematic review and meta-analysis, aiming to establish pooled estimates for survival outcomes of TILs based on their abundance and infiltrating location. A literature search of PubMed/Medline, Embase, Web of Science and the Cochrane Library was conducted. Studies that investigated the prognostic significance of generalized, CD8+, CD4+, FoxP3+, CD3+, and CD45O+ TILs in ESCC patients were included. Results: In pooled analysis, generalized TILs infiltrating the entire tumor mass were positively associated with disease-free survival (DFS), with a univariate-related hazard ratio (HR) of 0.630 (95% confidence interval (CI) 0.415-0.955), and also positively associated with overall survival (OS), with a univariate-related HR of 0.586 (0.447-0.770) and a multivariate-related HR of 0.621 (0.439-0.878). The pan-tumor, intra-tumor and peri-tumor CD8+ TILs had a favorable effect on OS, with univariate-related HRs of 0.733 (0.555-0.968), 0.797 (0.660-0.962), and 0.776 (0.635-0.948), respectively. Similar results were observed in CD8+ TILs that infiltrated the whole tumor mass, with a multivariate-related HR of 0.705 (0.524-0.947). CD4+, FoxP3+, CD3+, and CD45O+ TILs were not linked to DFS or OS. Subtypes and spatial locations of TILs seemed to influence study outcomes. Conclusions: Experimental and analytical methods of future studies should be carefully designed to avoid overestimating the effect of TILs on prognosis. Our meta-analysis confirms the prognostic efficacy of generalized TILs and CD8+ TILs in esophageal squamous cell carcinoma (ESCC) patients.